Cover Image, Volume 38, Number 8, November 2019. Issue 8 (18th October 2019) - Mathew, Seema; Guzmán Rojas, Rodrigo A.; Salvesen, Kjell A.; Volløyhaug, Ingrid
Abstract : The Front Cover : The cover image is based on the ORIGINAL CLINICAL ARTICLE Levator ani muscle injury and risk for urinary and fecal incontinence in parous women from a normal population, a cross‐sectional study by Seema Mathew et al., https://doi.org/10.1002/nau.24138 . Cover Credit : Cover image © Seema Mathew Images